Tumour of the ureter of horsehoe kidney – a case report - Tkocz, Michał; Szedel, Andrzej; Białożyt, Michał; Kupajski, Maciej (Contemporary Oncology/Współczesna Onkologia, 2008)
The authors present a patient with a horseshoe kidney in whom a primary tumour of the ureter gave rise to hydronephrosis. The patient was subjected to operative treatment to remove the left part of the horseshoe kidney together with the ureter and part of the urinary bladder.